Synthesis and mechanical properties of alumina slip casting from aluminium tri- hydrate (aL(oh)3) - Nurfarahin Binti Mohd. Nordin (School of Materials Engineering, University Malaysia Perlis, 2016)
This experiment was done to investigate the mechanical properties of synthesized Al(OH)3 for slip casting process. The Al(OH)3 precursor was synthesized by two process, calcinations of Al(OH)3 and leaching along with calcinations of Al(OH)3. Ceramics bodies were produced using those synthesized precursor by slip casting process with different sintering time and temperature. It is to see how the synthesized and sintering time and temperature governed the mechanical properties of ceramics bodies. The results showing that the mechanical properties of ceramics bodies by leached precursor produced better properties compared to ceramics bodies by calcined precursor. The mechanical properties were increase as the sintering temperature was increased but for sintering time the mechanical properties were dropping at longer sintering time and higher sintering temperature.